Distingsi Kaum Borjuis Dengan Kaum Proletar Dalam Novel “Wuthering Heights” Karya Emily Bronte - Nuraeni, Paridah; Saprudin, Saprudin; Susilawati, Lusi (KREDO : Jurnal Ilmiah Bahasa dan Sastra, 2021)
This research aims to describe the distinction or difference between the bourgeoisie and the proletariat which is described in Emily Bronte's novel Wuthering Heights which has a connection with one's social class. This research used the descriptive qualitative method. The approach used in this research is the sociology of literature approach with a focus on the study of social backgrounds. The data sources come from the novel Wuthering Heights by Emily Bronte. The data results are the form of sentences and paragraphs related to social class and social status. The data collection technique was done by observing the novel itself. Data analysis was performed by conducting a taxonomic analysis. The result of the research shows that the distinction of the bourgeoisie and the proletariat in Emily Bronte's novel Wuthering Heights lies in the power and wealth possessed by the bourgeoisie. Besides that, the way they look, behave, and speak reflects their social class. The proletariat is known as the workers. Meanwhile, the bourgeoisie is the people in power. This social class split occurred during the industrial revolution of the 19th century in England. Where these events also influenced the creation of the novel Wuthering Heights.